El hábeas data en el Ecuador. Análisis de las reglas jurisprudenciales dictadas por la Corte Constitucional. - Duarte Abarca, Bryan Gustavo (2024)
To the reader, this document has the purpose of reviewing and carrying out a detailed analysis of the sentences issued by the Constitutional Court of Ecuador: “No. 025-15-SEP-CC, 182-15-SEP-CC and No. 55-14-JD/ 20”, related to the jurisdictional guarantee of habeas data. In this sense, it is intended to understand the jurisprudential rules that have been developed in depth by the Constitutional Court for the protection of the rights of privacy and access to personal information; all this evidently contrasting from its history to the entry into force of the current Constitution of the Republic of Ecuador, as well as the legal reality of the same figure; detailing what changes it has gone through and according to what situations it has changed over time. For this purpose, first of all, a brief historical, conceptual and doctrinal description of the aforementioned guarantee will be made. The research examines the evolution of Habeas Data in the Ecuadorian context, highlighting its importance in the protection of privacy and control of personal information. Then, based on the study of the jurisprudence of the Court mentioned above, there is, on the one hand, solid and clear criteria regarding habeas data, and on the other, the decisions of the Constitutional Court are examined in detail, evaluating their scope and relevance in the safeguarding of constitutional rights. Finally, for the development of this academic work available to the reader, a methodology integrated by materials, techniques, research methods and documentary observation used in legal-doctrinal research and analysis, and in the study of Court decisions, is applied. Constitutional. In this way, upon completing this academic proposal, its final product is reflected in the conclusions and recommendations that must serve as a guide for the application of habeas data. This exercise, undoubtedly, enables the evolution and development of law in line with the advancement of society, and at the same time, contributes to the strengthening of legal culture at the national level.